2020
DOI: 10.1080/10717544.2020.1790693
|View full text |Cite
|
Sign up to set email alerts
|

Precise engineering of Gemcitabine prodrug cocktails into single polymeric nanoparticles delivery for metastatic thyroid cancer cells

Abstract: GLOBOCAN estimates 36 types of cancers in 185 countries based on the incidence, mortality, and prevalence in the year 2019. Nowadays, chemotherapy is the most widely used cancer treatment among immune, radio, hormone, and gene therapies. Here, we describe a very simple yet cost-effective approach that synergistically combines drug reconstitution, supramolecular nano-assembly, and tumor-specific targeting to address the multiple challenges posed by the delivery of the chemotherapeutic Gemcitabine (GEM) drug. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…MET-PLGA-PEG NPs also induced nuclei fragmentation and apoptosis in the treated cancer cells [122]. Other NPs which were reported to induce apoptosis in cancer cells are Nos-mPEG-PLGA NPs [117], NVA polymeric NPs [136], ANZ-PLNP NPs [118], 3A.1-loaded pH-sensitive NPs [132], CS-CPT-NPs [133], 5FU-Chrysin-PLGA-PEG-PLGA NPs [120], and Gemcitabine-loaded NPs conjugated with linoleic acid [143]. Nos-mPEG-PLGA NPs [117] has antiangiogenic properties while NVA polymeric NPs [136] inhibited cellular proliferation.…”
Section: Polymeric Nanomaterials Targeting Various Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…MET-PLGA-PEG NPs also induced nuclei fragmentation and apoptosis in the treated cancer cells [122]. Other NPs which were reported to induce apoptosis in cancer cells are Nos-mPEG-PLGA NPs [117], NVA polymeric NPs [136], ANZ-PLNP NPs [118], 3A.1-loaded pH-sensitive NPs [132], CS-CPT-NPs [133], 5FU-Chrysin-PLGA-PEG-PLGA NPs [120], and Gemcitabine-loaded NPs conjugated with linoleic acid [143]. Nos-mPEG-PLGA NPs [117] has antiangiogenic properties while NVA polymeric NPs [136] inhibited cellular proliferation.…”
Section: Polymeric Nanomaterials Targeting Various Cancersmentioning
confidence: 99%
“…Naringenin-loaded hyaluronic acid decorated PCL NPs also facilitated drug delivery in NSCLC cells [142]. Gemcitabine (GEM) NPs conjugated with linoleic acid (GEM NPs) have a high drug load, able to control the release of drug, and improve the intracellular uptake in thyroid cancer [143]. DTX-loaded NPs assisted the drug delivery to ovarian cancer [144].…”
Section: Polymeric Nanomaterials Targeting Various Cancersmentioning
confidence: 99%
“…These nanoparticles could be localized via lysosomes after incubation with differentiated thyroid cancer (DTC) cells and exhibited stronger cytotoxicity to DTC cells than free GEM, promoting apoptosis. 121 Furthermore, nanotechnology can facilitate the delivery of multiple chemotherapeutic drugs and targeted agents in the same nanoparticle, synergistically enhancing the anti-tumor effect. Studies have shown that folate receptor is highly expressed on tumor cell membranes.…”
Section: Nanomaterials As Carriers For Thyroid Cancer Treatmentmentioning
confidence: 99%
“…These nanoparticles could be localized via lysosomes after incubation with differentiated thyroid cancer (DTC) cells and exhibited stronger cytotoxicity to DTC cells than free GEM, promoting apoptosis. 121…”
Section: Nanomaterials In Thyroid Cancer Treatmentmentioning
confidence: 99%
“…These particles induced apoptosis in follicular thyroid carcinoma FTC133 and in papillary thyroid carcinoma B-CPAP cells. Because the nanoformulations were predicted to damage red blood cells, hemolysis could be excluded in hemolysis assays [83].…”
Section: Other Organic Materialsmentioning
confidence: 99%